Assessing College Life Adjustment of Students With Disabilities: Application of the PERMA Framework. (April 2018) - Tansey, Timothy N.; Smedema, Susan; Umucu, Emre; Iwanaga, Kanako; Wu, Jia-Rung; Cardoso, Elizabeth da Silva; Strauser, David
The clearest career path to the middle class generally involves access, and completion, of postsecondary education. However, persons with disabilities are less likely to enroll or graduate from college compared with their same-age peers without disabilities. The quality of life of students with disabilities, and their well-being, may be a root cause of low graduation rates. To flourish in life is to both feel good and function effectively. Seligman developed the Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment (PERMA) model that may be useful in understanding the well-being of individuals. The purpose of this study is to examine the factorial structure of the PERMA model in sample college students with disabilities and then examine the model's relationship with outcomes important to college adjustment such as academic achievement, relationship problems, stress, life satisfaction, and core self-evaluation. Ninety-seven college students with disabilities enrolled in Science, Technology, Engineering, and Mathematics (STEM) were recruited for the study. Findings support a one-factor solution for the PERMA measurement model. Furthermore, PERMA was negatively correlated with factors associated with college difficulty and positively associated with factors linked to college success. The PERMA model also demonstrated that well-being mediates the relationship between functional disability and life satisfaction. Implications for rehabilitation researchers and practitioners are reviewed.